12.4k views
4 votes
A.10D Simplify the expression
(x - 3)2

2 Answers

3 votes

Answer:

2x - 6

Explanation:

(x-3)2

2( x ) = 2x

2( - 3 ) = - 6

2x - 6

User Logman
by
4.9k points
3 votes


\implies {\blue {\boxed {\boxed {\purple {\sf { \: 2x - 6}}}}}}


\sf \bf {\boxed {\mathbb {Step-by-step\:explanation:}}}


\:(x - 3)2


\: 2x - 6

Note:-


\sf\red{PEMDAS\: rule.}

P = Parentheses

E = Exponents

M = Multiplication

D = Division

A = Addition

S = Subtraction


\bold{ \green{ \star{ \orange{Mystique35}}}}⋆

User Kingargyle
by
5.6k points